The illusion of aircrews' fatigue risk control - Samira Bourgeois-Bougrine (Transportation Research Interdisciplinary Perspectives, 2020)
In the fragmented European airline sector, companies are operating in a highly competitive environment amid rising cost of labour, fuel and airport fees. Fatigue risk management systems (FRMS) contribute to flexibly optimizing crew “utilization” through deviations and derogations from prescriptive European limits on duty times and rest durations. However, the flexibility gained comes at a price: it introduces an internal bureaucracy to mitigate the risks associated with crewmembers' fatigue and to develop, maintain and document fatigue related safety performance indicators. This paper questions the effectiveness of the FRMS framework and suggests that the bureaucratic process of the FRMS provides an illusion of fatigue risk control. More specifically four questions will be addressed: Why an operator needs an FRMS? Why the FRMS involves a bureaucratic process? What are the limits of the bureaucratic accountability of the FRMS and, finally, how might we manage fatigue risk effectively while keeping everyone happy, the shareholders as well as stakeholders?